Prognostic similarity between ovarian mucinous carcinoma with expansile invasion and ovarian mucinous borderline tumor: A retrospective analysis. Issue 32 (13th August 2021) - Hada, Taira; Miyamoto, Morikazu; Ishibashi, Hiroki; Matsuura, Hiroko; Sakamoto, Takahiro; Kakimoto, Soichiro; Iwahashi, Hideki; Suzuki, Rie; Sato, Kimiya; Tsuda, Hitoshi; Takano, Masashi
Abstract : Abstract: There is a similarity of histological features and survival between ovarian mucinous carcinoma (MC) with expansile invasion and ovarian mucinous borderline tumor (MBT). The aim of this study was to compare the clinical outcomes of MC with expansile invasion with those of MBT based on the 2020 World Health Organization (WHO) criteria. A pathological review was performed on patients with MC, ovarian MBT, and seromucinous borderline tumors that underwent surgery at our hospital between 1984 and 2019. Clinicopathological features were compared retrospectively between MC with expansile invasion and MBT. Among 83 cases of MC, 85 cases of MBT, and 12 cases of seromucinous borderline tumor, 25 MC cases with expansile invasion and 98 MBT cases were included through review. MC cases with expansile invasion were diagnosed with advanced International Federation of Gynecology and Obstetrics (FIGO) stages more frequently ( P = .02) than that of MBT cases. In addition, patients with MC with expansile invasion received adjuvant chemotherapy more often ( P < .01) than that of patients with MBT. There were no statistically significant differences in recurrence rate ( P = .10) between MC with expansile invasion and MBT. Progression-free survival (PFS) was worse in MC cases with expansile invasion than that in MBT cases ( P = .01). However, a multivariate analysis for PFS showed that histological subtype, FIGO stage, and adjuvant chemotherapy were not an independent prognostic factor. The prognostic outcome of MC with expansile invasion might mimic those of MBT. These results showed ovarian borderline tumor treatment could be applied to MC treatment.